An in-depth view of the metallicity distribution of the Small Magellanic Cloud - Piatti, Andres Eduardo (2023)
The spatial metallicity distribution of star clusters in the Small Magellanic Cloud(SMC) has recently been found to correlate as a V-shaped function with the semi-major axis of an elliptical framework proposed to assume a projected galaxy flattening.We report results on the impact that the use of such a framework can produce onour understanding of the SMC formation and its chemical enrichment. We show thatclusters with similar semi-major axes are placed at a very different distances fromthe SMC centre. The recently claimed bimodal metallicity distribution of clustersprojected on the innermost SMC regions and the V-shaped metallicity gradient fadeaway when actual distances are used. Although a large dispersion prevails, clustersolder than ∼ 1 Gyr exhibit a shallow metallicity gradient, caused by slightly differentspatial distributions of clusters younger and older than ∼ 4 Gyr; the former beingmore centrally concentrated and having a mean metallicity ([Fe/H]) ∼ 0.15 dex moremetal-rich than that of older clusters. This metallicity gradient does not show anydependence with the position angle, except for clusters placed beyond 11 kpc, whichare located in the eastern side of the galaxy.